IMPLEMENTASI HABITUASI SEKOLAH DALAM PEMBENTUKAN PROFIL PELAJAR PANCASILA PADA SISWA KELAS VI SD NEGERI 1 MONTONGSARI KENDAL - Siti Maghfiroh; A. Y. Soegeng Ysh; Joko Sulianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that drives this research is the impact of globalization. One of the negative impacts in the world of education includes the rise of bullying, brawls between students and cases of sexual abuse against children which are a weakness of the nation's character. in the formation of Pancasila student profiles. This study used a qualitative research type, the informants of this research were school principals, driving teachers, and class VI students at SD Negeri 1 Montongsari Kendal using interview, observation and documentation techniques. Data analysis used is data reduction, data presentation, and conclusion and verification. The results of this study are that SD Negeri 1 Montongsari Kendal has carried out various kinds of habituation in forming the profile of Pancasila students. The habituation carried out is adjusted to the six main characteristics of the Pancasila student profile, including: Faith, piety to God Almighty and noble character; global diversity; worked together; independent; critical reasoning; and creativity, the six main characteristics are interrelated with one another so as to form characters who practice Pancasila values in their daily lives. The application of habituation is carried out through programs that have been designed before the new school year begins. The habituation program is divided into programmed habituation, routine habituation and spontaneous habituation. Habituation that is carried out routinely also has a good impact on character as a Pancasila student. But even so, there are some students whose character is still not good. This is because there are still many obstacles experienced by teachers. In addition to obstacles, there are also many supporting factors in implementing habituation in forming a Pancasila student profile.